2006
DOI: 10.2174/157340006778018193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbid Anxiety Disorders in Schizophrenia Spectrum Disorders: A Literature Review

Abstract: Objective: We conducted a comprehensive review of the English language literature on the comorbidity of anxiety symptoms/disorders in schizophrenia spectrum disorders (SSDs) in order to determine: their prevalence rates in clinical and non-clinical populations, the temporal relationship of anxiety comorbidity to SSDs, and the effect of comorbidity on outcome.Results: Overall lifetime prevalence rates for any anxiety disorder ranged from 30% to 85% with most studies showing rates higher than in the general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 93 publications
(256 reference statements)
1
20
0
Order By: Relevance
“…A recent comprehensive review of anxiety disorders in the context of schizophrenia has shown that anxiety (when taken to mean any experience of clinically significant anxious symptoms) is present in 16%–85% of samples, with the overall rate for clinical studies (as opposed to epidemiological ones) averaging 50% . Similar findings have been reported using a sample of out‐patients, with 41.5% reaching criteria for a concurrent anxiety disorder .…”
Section: Introductionmentioning
confidence: 56%
“…A recent comprehensive review of anxiety disorders in the context of schizophrenia has shown that anxiety (when taken to mean any experience of clinically significant anxious symptoms) is present in 16%–85% of samples, with the overall rate for clinical studies (as opposed to epidemiological ones) averaging 50% . Similar findings have been reported using a sample of out‐patients, with 41.5% reaching criteria for a concurrent anxiety disorder .…”
Section: Introductionmentioning
confidence: 56%
“…In fact, it appears that the action mechanism of a specific gene is less important than its expression level in specific brain regions in the prediction of its relevance for behavioral processes. Secondly, the anxiety accompanying several mental diseases, such as depression and schizophrenia (Pokos and Castle, 2006), might be due to the brain expression level of the genes involved in the main symptoms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] With respect to particular AD, rates of panic disorder in schizophrenia are of the order of 5% to 35%. [14][15][16][17][18][19] Obsessivecompulsive disorder (OCD) also commonly co-occurs with schizophrenia. Studies have found 29% of an inpatient sample 17 and 37.5% of an outpatient sample 14 to have OCD in addition to schizophrenia.…”
Section: Introductionmentioning
confidence: 99%